All-Solution-Processed Quantum Dot Electrical Double-Layer Transistors Enhanced by Surface Charges of Ti 3 C 2 T x MXene Contacts - Kim, Hyunho; Nugraha, Mohamad I.; Guan, Xinwei; Wang, Zhenwei; Hota, Mrinal K.; Xu, Xiangming; Wu, Tom; Baran, Derya; Anthopoulos, Thomas D.; Alshareef, Husam N. (ACS nano, 2021)
Fully solution-processed, large-area, electrical double-layer transistors (EDLTs) are presented by employing lead sulfide (PbS) colloidal quantum dots (CQDs) as active channels and Ti C T MXene as electrical contacts (including gate, source, and drain). The MXene contacts are successfully patterned by standard photolithography and plasma-etch techniques and integrated with CQD films. The large surface area of CQD film channels is effectively gated by ionic gel, resulting in high performance EDLT devices. A large electron saturation mobility of 3.32 cm V s and current modulation of 1.87 × 10 operating at low driving gate voltage range of 1.25 V with negligible hysteresis are achieved. The relatively low work function of Ti C T MXene (4.42 eV) compared to vacuum-evaporated noble metals such as Au and Pt makes them a suitable contact material for -type transport in iodide-capped PbS CQD films with a LUMO level of ∼4.14 eV. Moreover, we demonstrate that the negative surface charges of MXene enhance the accumulation of cations at lower gate bias, achieving a threshold voltage as low as 0.36 V. The current results suggest a promising potential of MXene electrical contacts by exploiting their negative surface charges.